Larva migrans visceral. - Arencibia Pérez, José Manuel; Ortoño Mas, Laura; Corral García, Roberto; Fong Álvarez, Gladys; Vallejo Witoska, René (Revista Cubana de Pediatría, 2023)
Se presenta el caso de un escolar afectado por larva migrans visceral por Toxocara cati.